Sobre a aplicação de Gauss para hipersuperfícies de curvatura média constante na esfera - Silva, Adam Oliveira da (2009)
The objective of this dissertation is to show a similar result of Bernstein Theorem about minimal hypersurfaces in Euclidian space, that is, to show that that result is generalized to hypersurfaces of Sn+1 with constant mean curvature, whose Gauss image is contained in a closed hemisphere of Sn+1(Theorem 3.1). However, in the case where the hypersurface is minimal, we will use in the proof of this theorem a result about the characterization of the hyperspheres of Sn+1 among all complete hypersurfaces in Sn+1 in terms of their Gauss images (Theorem 2.1).